Prosedur Pembiayaan Musyarakah Mutanaqisah Pada Bank Syariah Indonesia KC Kuta Cane - Vera Ayu Ningsih Ritonga; Reni Ria Armayani Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Musyarakah mutanaqishah is musyarakah or syirkah ownership the assets (goods) or capital of one of the parties (shariq) are reduced due to gradual purchase by other parties. As well as a musyarakah agreement mutanaqishah is a combined contract between a musyarakah contract and a contract ijarah. Sharia syndicated financing is financing provided by two/more Islamic banks or financial institutions, with the same terms and conditions, using the same documents and administered by one bank. Regarding information on syndicated financing using a musyarakah agreement Mutanaqishah is still not widely known by the wider community until now This. So this research will focus on discussing contracts musyarakah mutanaqisah used in syndicated financing. Because This contract is a contract that needs to be socialized and more publicized the banking sector, because its existence is not widely known by the public common among other contracts which are also used for syndicated financing in sharia banking in Indonesia, after previously using contracts murabahah and ijarah mun tahiya bit tamlik.